Perancangan Sistem Penunjang Keputusan Investasi Daerah Berbasis Webgis di Provinsi Sumatera Barat (Studi Kasus Badan Koordinasi Penanaman Modal Provinsi Sumatera Barat) - Difana Meilani; Ryan Amirulfiras (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2015)
The implementation of decision support system will be applied to support the regional investment of West Sumatera by providing a feasibility study analysis; exclusively the aspects of economic and financial criteria. This research was carried out in West Sumatera Regional Investment Coordinating Board as the authorities of regional investment licensing and controlling. The first step in designing a decision support system is conducting Pre – Study. It consists of literature study and pre–design study related to the field of study. Next step is using Unified Modeling Language (UML) method to provide, represent and visualize the system. The basic model of the financial feasibility study is implemented by using the predetermined assumption as the scope of the best system performance. The system design which is implemented uses the Web and GIS concept. Otherwise, the expected result from the research is the application is able to calculate the basic data from financial feasibility aspect into needed information in order to analyze the feasibility of any investments. The result should be converted into Net Present Value, Benefit Cost Ratio, Internal Rate of Returns, and Payback Period value. The last step of the research is verification and validation in order to make sure the ability of application accommodating the pre -design system requirements. The result of verification and validation is able to accommodate the pre -designsystem requirements conclusively.